4 - Ethnicity, Governance and Prevention of Conflict: State of the Issue and Research Perspectives: 10.4314/ad.v24i3.22127 - Aseka , Eric Masinde (Africa Development, 1999)
The paper presents the issues of ethnicity, governance and prevention of conflicts in terms of their political management through the proper exercise of power. Conflict cannot be prevented, it can only be managed. The crucial determining factor in ethnic, gender and class relations is power. The paper traces notions of power in the works of various philosophers and outlines the significance of perceiving the impact of paradigmatic shifts on political discourse. These shifts are perceived as intellectual itineraries from structural-functionalism to the contemporary North America Critical Theory and postmodernist theory. The problematic of ethnicity is posed within debates emanating from the ensuing perspectival contests and paradigmatic struggles. The moral economy, rational choice, and subaltern approaches are also interrogated and critiqued. The paper contends that when the structures and procedures of democratic governance are undermined, political legitimacy also gets compromise.